2018
DOI: 10.18408/ahuri-7313201
|View full text |Cite
|
Sign up to set email alerts
|

Supporting affordable housing supply: inclusionary planning in new and renewing communities

Abstract: Related reports and documents Inquiry into increasing affordable housing supply: evidence-based principles and strategies for Australian policy and practice https://www.ahuri.edu.au/research/research-in-progress/inquiry-73130.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…Introduced in 2005, South Australia's inclusionary planning approach has become an important lever for preserving affordability, particularly in new-release greenfield areas and regional areas (Gurran, Gilbert et al 2018).…”
Section: Capital City Strategic Planning Frameworkmentioning
confidence: 99%
“…Introduced in 2005, South Australia's inclusionary planning approach has become an important lever for preserving affordability, particularly in new-release greenfield areas and regional areas (Gurran, Gilbert et al 2018).…”
Section: Capital City Strategic Planning Frameworkmentioning
confidence: 99%
“…Our review, particularly of the most recent international experience in the UK and US, confirmed that inclusionary planning has continued to be an important mechanism for ensuring that housing development processes deliver homes across the continuum of housing need. Our analysis of recent data found that, in 2015-16, nearly 13,000 dwellings, amounting to around 43 per cent of total affordable housing supply in England, were delivered through the planning system in a diversity of products from affordable (discount market) rent, affordable and shared ownership, and social housing (Gurran, Gilbert et al 2018 ). Affordable housing contributions are negotiated under the English discretionary planning system, but within a strong mandate for delivering affordable homes in relation to local development plans, housing strategies, and market conditions.…”
Section: Recent International Practice In Planning For Affordable Houmentioning
confidence: 94%
“…The NSW model also includes some planning system incentives to promote lower cost market housing, such as boarding houses. In other states, planning concessions are able to support affordable housing development, although on a limited basis (Gurran, Gilbert et al 2018 ). There is a need to assess the outcomes of existing planning approaches to affordable housing, if these practices are to be extended.…”
Section: Local Initiatives and Inclusionary Planningmentioning
confidence: 99%
See 2 more Smart Citations